HUBUNGAN KARAKTERISTIK RUMAH DENGAN KEJADIAN PENYAKIT TUBERKULOSIS PARU DI PUSKESMAS SIMPANG KIRI KOTA SUBULUSSALAM TAHUN 2012 - Melisah Pitri Siregar; wirsal hasan; Taufik Ashar (Lingkungan dan Kesehatan Kerja, 2013)
Corelation of house characteristic with the prevalence of pulmonary tuberculosis at public health centre  Simpang Kiri Subulussalam city 2012. Pulmonary Tuberculosis is a communicable disease which is caused by mycobacterium tuberculosis that lives in high humidity place, and house in one of media that gives high influence to the mycobacterium tuberculosis’s growth and its transmitting if the condition do not complete the term of health. Tuberkulosis bacteria can lives for weeks depend on the present of ultraviolet, the condition of ventilation, humidity, temperature and over crowding. The aim of this research was for determining the relation between the characteristics of house with the prevalence of pulmonary tuberculosis.The design of this research was Case Control. Total samples of this research was 50 respondents which is consist of 25 respondents for case that as the sufferer of pulmonary tuberculosis which recorded on the medical record of public health centre Simpang Kiri Kota Subulussalam city, and 25 respondents for Control, that was the people who lives around the sufferer of pulmonary tuberculosis by matching the characteristics age and gender with case. The data was analiyzed by Chi Square with degree of confidence was 5 %. Accourding to the result of this research, there was a significant differend between the characteristics of citizen’s house who suffer from pulmonary tuberculosis. With the citizens who didn’t suffer from it. The data shows, that Odds Ratio Of the density of living is 13,5, ventilation is 30,5, type of floor is 22,1, lighting is 9,3, temperature is 27,5 and humidity is 84,4 it is estimated that the characteristic of citizen’s house who didn’t suffer from it this condition indicate that there is relation between the characteristic of house with the prevalence of pulmonary tuberculosis in public health centre Simpang Kiri area Subulussalam city in 2012. Keyword : Characteristic of house, Pulmonary Tuberculosis